Effect of Electric Fields on Silicon-Based Monolayers - Li, Tiexin; Peiris, Chandramalika; Dief, Essam; MacGregor, M.; Ciampi, Simone; Darwish, Nadim (AMER CHEMICAL SOC, 2022)
Electric fields can induce bond breaking and bond forming, catalyze chemical reactions on surfaces, and change the structure of self-assembled monolayers on electrode surfaces. Here, we study the effect of electric fields supplied either by an electrochemical potential or by conducting atomic force microscopy (C-AFM) on Si-based monolayers. We report that typical monolayers on silicon undergo partial desorption followed by the oxidation of the underneath silicon at +1.5 V vs Ag/AgCl. The monolayer loses 28% of its surface coverage and 55% of its electron transfer rate constant (ket) when +1.5 V electrochemical potential is applied on the Si surface for 10 min. Similarly, a bias voltage of +5 V applied by C-AFM induces complete desorption of the monolayer at specific sites accompanied by an average oxide growth of 2.6 nm when the duration of the bias applied is 8 min. Current-voltage plots progressively change from rectifying, typical of metal-semiconductor junctions, to insulating as the oxide grows. These results define the stability of Si-based organic monolayers toward electric fields and have implication in the design of silicon-based monolayers, molecular electronics devices, and on the interpretation of charge-transfer kinetics across them.